Till surgery do us part: unexpected bilateral kissing molars - Narayanankutty Anish; Velayudhannair Vivek; Sunila Thomas; Vineet Alex Daniel; Jincy Thomas; Prasanna Ranimol (Clinics and Practice, 2015)
The occurrence impacted teeth, single or multiple is very common. But, phenomenon of kissing molars is an extremely rare phenomenon. Mandibular third molars are the most common impacted teeth. Mandibular first or second molars does not share the same frequency of occurrence. But, there are rare cases in which the occlusal surfaces of impacted molars are united by the same follicular space and the roots point in the opposite direction, and are termed as kissing molars. Sometimes, these teeth will be associated with pathologies. This article reports a rare case of mandibular bilateral kissing molars.